Implementing lean principles for digital archiving of student projects: A case study in higher education - Sarawan, Kamthorn; Khalwipat, Rajarat; Daengkasai, Witthaya; Khumla, Pornsiri (Sustainable Engineering and Innovation, 2025)
This study applies lean principles to address organizational challenges by designing and developing a digital archiving system for student projects in higher education. The primary objective is to transition the case study institution from paper-based project documentation to a sustainable, paperless digital system, reducing the consumption of approximately 1,000–1,500 printed project books annually. We collected data from various stakeholders to construct an information system that utilized the PHP programming language and the MySQL database system. After the system’s development, we evaluated its effectiveness across seven dimensions using input from thirty users. We obtained a mean score of 4.07. The application of lean ideas to evaluate and set standards for the management of an organization has the potential to foster sustainability.